An Alkynyl-Fucose Halts Hepatoma Cell Migration and Invasion by Inhibiting GDP-Fucose-Synthesizing Enzyme FX, TSTA3 - Kizuka, Yasuhiko; Nakano, Miyako; Yamaguchi, Yoshiki; Nakajima, Kazuki; Oka, Ritsuko; Sato, Keiko; Ren, Chien-Tai; Hsu, Tsui-Ling; Wong, Chi-Huey; Taniguchi, Naoyuki (Cell chemical biology, 2017)
Fucosylation is a glycan modification critically involved in cancer and inflammation. Although potent fucosylation inhibitors are useful for basic and clinical research, only a few inhibitors have been developed. Here, we focus on a fucose analog with an alkyne group, 6-alkynyl-fucose (6-Alk-Fuc), which is used widely as a detection probe for fucosylated glycans, but is also suggested for use as a fucosylation inhibitor. Our glycan analysis using lectin and mass spectrometry demonstrated that 6-Alk-Fuc is a potent and general inhibitor of cellular fucosylation, with much higher potency than the existing inhibitor, 2-fluoro-fucose (2-F-Fuc). The action mechanism was shown to deplete cellular GDP-Fuc, and the direct target of 6-Alk-Fuc is FX (encoded by TSTA3), the bifunctional GDP-Fuc synthase. We also show that 6-Alk-Fuc halts hepatoma invasion. These results highlight the unappreciated role of 6-Alk-Fuc as a fucosylation inhibitor and its potential use for basic and clinical science. [Display omitted] •6-Alkynyl-fucose, a widely used fucosylation probe, strongly inhibits fucosylation•6-Alkynyl-fucose competitively inhibits GDP-fucose synthetase FX•6-Alkynyl-fucose halts hepatoma invasion•6-Alkynyl-fucose is a powerful tool for modulating cellular fucosylation Fucose sugar is involved in cancer and inflammation. Kizuka et al. found that a fucose alkyne strongly inhibits cellular fucosylation. The compound selectively inhibits GDP-fucose synthetase FX and can be applied to glycan-related diseases.